Planetary Spacecraft Navigation - Miller, James; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook introduces the theories and practical procedures used in planetary spacecraft navigation. Written by a former member of NASA's Jet Propulsion Laboratory (JPL) navigation team, it delves into the mathematics behind modern digital navigation programs, as well as the numerous technological resources used by JPL as a key player in the field. In addition, the text offers an analysis of navigation theory application in recent missions, with the goal of showing students the relationship between navigation theory and the real-world orchestration of mission operations.
Preface -- Chapter 1: Equations of Motion -- Chapter 2: Force Models -- Chapter 3: Trajectory Design -- Chapter 4: Trajectory Optimization -- Chapter 5: Probability and Statistics -- Chapter 6: Orbit Determination -- Chapter 7: Measurement Systems -- Chapter 8: Navigation System -- Chapter 9: Navigation Analysis -- Answers to Exercises -- Index.
Keywords: Aerospace engineering; Astronautics; Solar system; Software engineering; Computer science -- Mathematics; Aerospace Technology and Astronautics; Space Physics; Software Engineering; Mathematical Applications in Computer Science